Bzd9l1: Elucidation Of Its Anti-angiogenic Potential In In-vitro And In-vivo Colorectal Cancer Models - Subramaniam, Ayappa V. (2023)
Colorectal cancer (CRC) is the third most common cancer globally. CRC depends largely on angiogenesis for growth and metastasis. Much effort has been made to selectively target the angiogenic pathways to restrain tumour growth. However, some CRC patients become resilient to these anti-angiogenic drugs and standard therapies. The class III histone deacetylase family of sirtuins (SIRTs) has been closely linked to cancer progression but less is known about its activity in regulating tumour angiogenesis. BZD9L1 is a novel sirtuin inhibitor with demonstrated anti-cancer activities. This study aimed to investigate the anti-angiogenic potential of BZD9L1 on EA.hy926 endothelial cells (EC) in vitro and HCT116 tumour xenograft nude mice. The in vitro experiments comprised of cell viability assay, scratch wound assay, tube formation assay, spheroid sprouting assay, western blotting, angiogenesis array, cell cycle and apoptosis analysis via flow cytometry and finally, indirect co-culture model. Nude mice tumour xenograft model was used for the in vivo study, where hematoxylin and eosin staining was done to study the percentage of necrosis in the tumour section and immunohistochemistry was conducted to investigate the protein expression of Ki67 and CD34. BZD9L1 was shown to reduce cell viability, cell migration, tube formation, and spheroid sprouting of EC. BZD9L1 at 10μM was also shown to inhibit SIRT2 and SIRT3 protein in EA.hy926 cells. Angiogenesis array results revealed that the compound reduces the cytokine concentration of Angiogenin, bFGF, PDGF-BB, and PIGF significantly (P * < 0.05) compared to the control group